Video double-lumen tube for one lung ventilation: implementation and experience in 343 cases of routine clinical use during the first 20 months of the SARS-CoV-2 pandemic - Irouschek, Andrea; Schmidt, Joachim; Birkholz, Torsten; Sirbu, Horia; Moritz, Andreas (Journal of Cardiothoracic Surgery, 2024)
Background: Double-lumen tubes (DLTs) are the preferred device for lung isolation. Conventional DLTs (cDLT) need a bronchoscopic position control. Visualisation of correct DLT positioning could be facilitated by the use of a video double-lumen tube (vDLT). During the SARS-CoV-2-pandemic, avoiding aerosol-generation was suggesting using this device. In a large retrospective series, we report both general and pandemic related experiences with the device. Methods: All anesthesia records from patients aged 18 years or older undergoing surgery from April 1st, 2020 to December 31st, 2021 in the department of thoracic surgery requiring intraoperative lung isolation were analyzed retrospectively. Results: During the investigation period 343 left-sided vDLTs (77.4%) and 100 left-sided cDLTs (22.6%) were used for one lung ventilation. In the vDLT group bronchoscopy could be reduced by 85.4% related to the cDLT group. Additional bronchoscopy to reach or maintain correct position was needed in 11% of the cases. Other bronchoscopy indications occured in 3.6% of the cases. With cDLT, in 1% bronchoscopy for other indications than conforming position was observed. Conclusions: The Ambu® VivaSight™ vDLT is an efficient, easy-to-use and safe airway device for the generation of one lung ventilation in patients undergoing thoracic surgery. The vDLT implementation was achieved easily with full interchangeability to the left-sided cDLT. Using the vDLT can reduce the need for aerosol-generating bronchoscopic interventions by 85.4%. Continuous video view to the carina enabling position monitoring of the DLT without need for bronchoscopy might be beneficial for both employee’s and patient’s safety.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Double-lumen tube; One lung ventilation; SARS-CoV-2; Thoracic surgery; Video double-lumen tube